International Learning Partnership: Living History and Adult Education in the Museum - Susanne Wiermann (EXARC, 2012)
Many archaeological open-air museums and museums with indoor reconstructions choose to interpret history using the method of ‘living history’, or re-enactments. If one only counts the German references, there is wide variety of terms used by museums when they talk of ‘living history’. The phrase ‘living history’ is often used synonymously with ‘lived history’, ‘played history’, ‘museum theatre’, ‘history theatre’, ‘staged-managed history’, et cetera.